Precision and accuracy of four handheld blood lactate analyzers across low to high exercise intensities - Mentzoni, F.; Skaugen, M.; Eythorsdottir, I.; Roterud, S.; Spro Johansen, E.; Losnegard, T. (European Journal of Applied Physiology, 2024)
Purpose To evaluate the precision and accuracy in measured blood lactate concentrations among four commonly used handheld lactate analyzers compared to two stationary analyzers.